1993
DOI: 10.1007/bf01185278
|View full text |Cite
|
Sign up to set email alerts
|

Determination of flavone C-glycosides in tea

Abstract: An HPLC method for the determination of flavone C-glycosides (FCG) from black tea has been developed. Sample clean-up was accomplished by means of polyamide column chromatography, followed by enzyme hydrolysis of interfering compounds such was flavonol glycosides and a second polyamide column chromatographic step. Using HPLC with gradient elution and photodiode array detection eight FCG were separated. Seven FCG were isolated by means of preparative HPLC. Identification was carried out using co-chromatography,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 1 publication
1
40
0
1
Order By: Relevance
“…Neither of these studies detected flavones for three possible reasons: co-elution of the flavones with flavonols, hydrolysis may have destroyed some of the flavone aglycones or not hydrolyzed the C-glycosides of flavones, and what little was present was below the limit of detection. The third study (Engelhardt et al, 1993), which measured the presence of flavone glycosides, was specific and thorough. There were 39 flavone datapoints, 32 for black (80%), four for green (10%), two for oolong (5%), and two for Pu'er teas (5%).…”
Section: à49mentioning
confidence: 99%
“…Neither of these studies detected flavones for three possible reasons: co-elution of the flavones with flavonols, hydrolysis may have destroyed some of the flavone aglycones or not hydrolyzed the C-glycosides of flavones, and what little was present was below the limit of detection. The third study (Engelhardt et al, 1993), which measured the presence of flavone glycosides, was specific and thorough. There were 39 flavone datapoints, 32 for black (80%), four for green (10%), two for oolong (5%), and two for Pu'er teas (5%).…”
Section: à49mentioning
confidence: 99%
“…Engelhardt et al (1992) have reported that the profile of FG may be characteristic of the variety of fresh leaf used in tea manufacture. They examined only two teas from China, one in which quercetin derivatives dominated Traces of theaflavins were found in the Quingmao tea but were not detected in the steamed tea suggesting that there had been some PPO activity prior to firing but that such activity had been inhibited by the steaming process.…”
Section: Brewingmentioning
confidence: 99%
“…10,11) In addition, phenolic acids (chlorogenic acid, gallic acid, and caffeic acid) and purine alkaloids (caffeine, theobromine, and theophylline) are contained in green tea. 10) Green tea is one of the beneficial herbal ingredients for dental health.…”
mentioning
confidence: 99%